2015
DOI: 10.1002/2015jd023126
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the global warming hiatus on Andean temperature

Abstract: The recent hiatus in global warming is likely to be reflected in Andean temperature, given its close dependence on tropical Pacific sea surface temperature (SST). While recent work in the subtropical Andes has indeed documented a cooling along coastal areas, trends in the tropical Andes show continued warming. Here we analyze spatiotemporal temperature variability along the western side of the Andes with a dense station network updated to 2010 and investigate its linkages to tropical Pacific modes of variabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
122
0
13

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 196 publications
(146 citation statements)
references
References 54 publications
11
122
0
13
Order By: Relevance
“…We have not investigated thermal conditions but the perceived increase in the frequency of ground frosts in the early growing season (as stated by some farmers) contradicts increasing (minimum) temperatures as reported by Schauwecker et al (2014) or in Vuille et al (2015). The increases in minimum temperatures are reported to be most pronounced in the dry and early wet season.…”
Section: Discussionmentioning
confidence: 99%
“…We have not investigated thermal conditions but the perceived increase in the frequency of ground frosts in the early growing season (as stated by some farmers) contradicts increasing (minimum) temperatures as reported by Schauwecker et al (2014) or in Vuille et al (2015). The increases in minimum temperatures are reported to be most pronounced in the dry and early wet season.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the largescale drivers of this retreat, such as increasing temperature (Vuille and Bradley, 2000;Bradley et al, 2009;Schauwecker et al, 2014;Vuille et al, 2015) or potential changes in the spatiotemporal characteristics of snowfall (Vuille and Ammann, 1997;Mernild et al, 2016;Saavedra et al, 2016), thereby altering the glacier's energy and mass balance, have been widely studied and discussed. Hence the goal of this paper is not to provide yet another detailed review of these observed changes, but rather to look ahead as to what impacts the region will face over the coming decades as glaciers continue to retreat and some eventually disappear.…”
Section: Introductionmentioning
confidence: 99%
“…There is, however, a trend toward slightly drier conditions on the Western cordillera of the Andes in southern Peru and western Bolivia (Vuille et al 2003). Increased NDVI across the study area is more likely due to a temperature increase of 0.9-0.15 ∘ C per decade since 1939 (Vuille & Bradley 2000;Vuille et al 2003Vuille et al , 2015Bradley et al 2006;Thibeault et al 2010;Seiler et al 2013). High-elevation biomes are particularly sensitive to increased temperature, with species or whole vegetation zones expected to migrate to higher elevations (Benniston 2003) provided suitable soils are available (Lee et al 2005).…”
Section: Discussionmentioning
confidence: 99%